Crohn's Disease: advantages of the Konos-S surgical technique (Research, Society and Development, 2022)
Introduction: Crohn's Disease (CD) belongs to the group of diseases called Inflammatory Bowel Diseases (IBD). CD is an inflammatory disease characterized by idiopathic, local and chronic nonspecific inflammation, currently the real cause is still unknown. The recurrence of anastomosis after intestinal resection is one of the most significant problems in the management of CD, recently a new surgical technique was described and used to reduce recurrence, the Konos-S technique described by Konos et al. (2011). Objective: To carry out a systematic review of the literature to describe Crohn's disease and the use of the Konos-S surgical technique for the treatment of the disease. Methodology: This study is a systematic review of the literature on the main search platforms for scientific articles: ScienceDirect, PubMed, SciELO, BIREME, from 2011 to 2022, 18 articles were selected. Results and Discussion: Kono and colleagues introduced into surgery their unique surgical technique to reduce the risk of surgical recurrence of the anastomosis is a hand-stitched end-to-end functional antimesenteric anastomosis. Some clinical studies have demonstrated the effectiveness of the technique in significantly reducing anastomotic and endoscopic recurrence, as it is able to preserve innervation and blood supply, important factors for proper healing of the anastomosis, with a lower risk of reoperation. However, more research is needed to universally validate Konos-S surgery for patients with an indication, as the treatment approach must be personalized for CD cases and complications must be analyzed individually for the patient.